Proclamation of Ferdinand VI in Cusco (23 September 1747): Art and Politics - Kubiak, Ewa (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
The article analyses the royal proclamation of Ferdinand VI in Cusco (Peru) which took place on 23 September 1747, on the birthday of the king. A reconstruction of the celebration was possible thanks to two sources: the city chronicle written in the mid-eighteenth century by Diego de Esquivel y Navía and an occasional print containing a description of the ceremony by José Antonio Santander (1748). The article discusses three aspects of the presented celebrations. First of all, it presents the general context, i.e. the problem of festival celebrations related to the royal family as a part of the Spanish crown policy. Secondly, it details artistic issues related to the celebrations. It includes a description of the artistic setting with the features of occasional architecture and ephemeral painting. Finally, the article examines the local, social and political contexts of the celebrations, read as a manifestation of the city’s emancipation efforts based on the emphasis of Cusco’s antiquity and its rich imperial tradition in the Pre-Hispanic period.